Effectiveness of the Problem-Based Learning (PBL) Method to Increase Students' Knowledge and Attitudes About Early Marriage - Sri Ayomi; Ayesha Hendriana Ngestiningrum; Tutiek Herlina (Knowledge Dynamics, 2024)
Background: High number of teenage marriages is a very worrying phenomenon because it causes various negative impacts on both reproductive health and social life. Indonesia is ranked second in ASEAN and eighth in the world for cases of early marriage. In the Mlarak sub-district, Ponorogo Regency, 8% of marriages were under 19 years of age. The purpose of the study was to determine the effectiveness of the Problem Based Learning (PBL) method to increased students' knowledge and attitudes about early marriage. Method: Research design was pre- experimental with a pretest - post test one group design. The sample was class VIII SMP Negeri 1 Mlarak, Ponorogo Regency, taken by proportional random sampling technique followed by Simple Random Sampling as many as 60 students. Collecting data using a questionnaire instrument. The independent variable is the PBL method while the dependent variable is knowledge and attitudes about early marriage. Data analysis used Paired Sample T Test with 0.05. Results: The results showed there is increase in the average knowledge of student by 14.08 and student attitudes by 12.2 after using the Problem Based Learning method. The results of the Paired Sample T Test 0.000 for the knowledge variable and 0.000 for the attitude variable, which means Ho is rejected and Ha is accepted. Conclusion: PBL method is effective in increasing knowledge about early marriage. The PBL method is effective in increasing attitudes about early marriage. Suggestions for teenagers to increase their knowledge about early marriage so that students' attitudes about early marriage can increase.